ANALYSIS AND CHARACTERIZATION OF SILICA OF PALM STRACH WASTE (ARENGA PINNATA) WITH COPRECIPITATION METHOD - Ruth Ramayani Pasaribu; Erna Frida; Susilawati (RADJA PUBLIKA, 2026)
Palm starch waste obtained from the Aci Kawung vermicelli flour factory in Ciamis, Indonesia, poses an environmental problem that also impacts the health of the surrounding community, thus requiring an effective treatment method. Silica synthesis from sago starch waste was performed using a coprecipitation method with 2M HCl. This study aimed to characterize the silica from sago starch waste using X-ray fluorescence (XRF) analysis to determine the elements, scanning electron microscopy (SEM) to determine the morphology, and a particle size analyzer (PSA) to determine the particle size of the silica. Sample preparation involved determining the weight of the raw material, washing the raw material, followed by physical and chemical activation through burning, calcination, mixing, and grinding, as well as chemical activation by washing with 2M HCl. XRF results showed that the main phase of the sample was SiO₂ at 68.90%. The silica itself can be utilized in wastewater adsorption. SEM analysis clearly shows numerous pores distributed evenly, which are beneficial for wastewater treatment; these evenly distributed pores are useful for adsorbing heavy metals such as Pb, Zn, Mn, and Fe. Additionally, PSA results indicate a particle size of 2.46 μm. This study holds potential for the development of bionanoadsorbent raw materials for water treatment.